Conversion to below-elbow cast after 3 weeks is safe for diaphyseal both-bone forearm fractures in children: A multicenter randomized controlled trial involving 127 children. (October 2013) - Colaris, Joost W; Allema, Jan Hein; Biter, L Ulas; Reijman, Max; Ven, Cees P van de; Vries, Mark R de; Bloem, Rolf M; Kerver, Albert J H; Verhaar, Jan A N
Abstract : Background It is unclear whether it is safe to convert above-elbow cast (AEC) to below-elbow cast (BEC) in a child who has sustained a displaced diaphyseal both-bone forearm fracture that is stable after reduction. In this multicenter study, we wanted to answer the question: does early conversion to BEC cause similar forearm rotation to that after treatment with AEC alone? Children and methods Children were randomly allocated to 6 weeks of AEC, or 3 weeks of AEC followed by 3 weeks of BEC. The primary outcome was limitation of pronation/supination after 6 months. The secondary outcomes were re-displacement of the fracture, limitation of flexion/extension of the wrist and elbow, complication rate, cast comfort, complaints in daily life, and cosmetics of the fractured arm. Results 62 children were treated with 6 weeks of AEC, and 65 children were treated with 3 weeks of AEC plus 3 weeks of BEC. The follow-up rate was 60/62 and 64/65, respectively with a mean time of 6.9 (4.7–13) months. The limitation of pronation/supination was similar in both groups (18 degrees for the AEC group and 11 degrees for the AEC/BEC group). The secondary outcomes were similar in both groups, with the exception of cast comfort, which was in favor of the AEC/BEC group. Interpretation Early conversion to BEC cast is safe and results in greater cast comfort.